2007
DOI: 10.1017/s1481803500015165
|View full text |Cite
|
Sign up to set email alerts
|

Integrating nurse practitioners into Canadian emergency departments: a qualitative study of barriers and recommendations

Abstract: Objective: The objective of this study was to identify the facilitators and barriers associated with integrating nurse practitioners (NPs) into Canadian emergency departments (EDs) from the perspectives of NPs and ED staff. Methods: We conducted 24 semi-structured interviews with key multidisciplinary stakeholders in 6 Ontario EDs to gain a broad range of perspectives on implementation issues. Data were analyzed using a grounded-theory approach. Results: Qualitative analysis of the interview data revealed 3 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 16 publications
3
51
0
Order By: Relevance
“…56,57 Lack of understanding of scope of practice and practitioner competence is a recurring theme in many studies of interprofessional care. 58 -61 This study demonstrates that when role is better defined, as it was at the 6-month point, physicians had less concern about NPs' scope of practice and liability.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Lack of understanding of scope of practice and practitioner competence is a recurring theme in many studies of interprofessional care. 58 -61 This study demonstrates that when role is better defined, as it was at the 6-month point, physicians had less concern about NPs' scope of practice and liability.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the small numbers involved in the studies (although some authors talk about saturation sampling) (Fisher et al, 2006) the findings are not safely generalisable to the wider national or international health care population. Despite this, the findings of Tye and Ross (2000) have been echoed in subsequent studies (Currie and Crouch, 2008;Thrasher and Purc-Stephenson, 2007) although Fisher et al (2006) did report some findings which countered those of Tye and Ross (2000) in that the ENPs interviewed thought of the role as an 'easy life', and thought that a positive recruitment issue would be the ability of senior nurses to get away from working night and weekend shifts.…”
Section: Healthcare Professionals' Perceptions Of the Rolesmentioning
confidence: 91%
“…Nine studies were identified that explicitly examined the perceptions of healthcare professionals regarding non-medical roles in emergency care (see Table 4) (Currie and Crouch, 2008;McGee and Kaplan, 2007;Thrasher and Purc-Stephenson, 2007;Lee and Bailey, 2007;Mason et al, 2007;Fisher et al, 2006;Griffin and Melby, 2006;Martin and Considine, 2005;Tye and Ross 2000). A characteristic of the majority of studies is that they involve small numbers of staff apart from the studies which used a validated questionnaire using a Likert scale which measured attitudes and knowledge of the new roles Bailey, 2007, Griffin andMelby 200 andConsidine, 2005).…”
Section: Healthcare Professionals' Perceptions Of the Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of the awareness of the NP role by nurses, doctors, allied health and patients is perceived as a barrier to role progression and sustainability throughout the literature (Appel and Malcolm, 2002;Clarin, 2007). For example, a study by Thrasher and Purc-Stephenson (2007) found that some registered nurses found it difficult performing tasks for patients being cared for by a NP citing confusion surrounding the NP role as the cause of the disagreement. Our results indicated that this was not the case within Victorian EDs.…”
Section: (14%)mentioning
confidence: 99%